Analysis of Social Impacts of Establishing a Chili Floss Production Facility on the Local Community (a Case Study of Hiyung Village, Tapin Regency) - Rachman, Zamhuri; Ahmad Nur Rohim (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the impact of the development of the Hiyung Bird's Eye Chili Floss Production House on the social life of the surrounding community in Hiyung Village, Tapin Regency. This production house was developed by the Karya Baru Farmers Group as an innovation to maintain the availability and increase the added value of local bird’s eye chili. The study was conducted using a qualitative approach with data collection methods through interviews, observations, and documentation involving farmers and farmers group administrators in Hiyung Village. The results indicate that the existence of the Production House has significantly contributed to improving the local community’s economy, stabilizing bird’s eye chili prices during harvest seasons, and encouraging social changes including education, culture, religion, and social interaction. Additionally, this development strengthens the values of mutual cooperation (gotong royong) and social solidarity in the village. Analysis using Talcott Parsons’ AGIL theory explains that the community is able to adapt, achieve common goals, maintain social integration, and preserve positive social behavior patterns through the presence of this Production House. This study is expected to serve as a reference for the development of small and medium enterprises and community social programs in rural areas.